2009
DOI: 10.1016/j.jvs.2008.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Staged endovascular treatment of bilateral ruptured and intact ovarian artery aneurysms in a postmenopausal woman

Abstract: Ovarian artery aneurysms have rarely been reported in the literature, with almost all being unilateral and occurring in the peripartum period. We herein describe a unique case of a postmenopausal patient with a ruptured ovarian aneurysm and an intact contralateral aneurysm that were both successfully treated by endovascular techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 7 publications
(20 reference statements)
1
21
0
Order By: Relevance
“…Several factors have been implicated, including hemodynamic changes such as increased blood volume and cardiac output as well as hormonal changes predisposing to aneurysm formation [1][2][3][4]. We have been able to find only seven reported cases of ovarian artery pseudoaneurysms in postmenopausal patients [2][3][4][5][6][7][8]. Two additional cases were reported in females of age 44 and 48, the first two years after a cesarean section [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been implicated, including hemodynamic changes such as increased blood volume and cardiac output as well as hormonal changes predisposing to aneurysm formation [1][2][3][4]. We have been able to find only seven reported cases of ovarian artery pseudoaneurysms in postmenopausal patients [2][3][4][5][6][7][8]. Two additional cases were reported in females of age 44 and 48, the first two years after a cesarean section [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneous rupture of an ovarian artery aneurysm is extremely rare. Our review of the published work revealed 21 cases of ovarian artery aneurysm dating back to 1963, as shown in Table . The age of the subjects ranged from 23 to 69 years, and 14 of the 21 cases were associated with pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with retroperitoneal hemorrhage due to spontaneous rupture of an ovarian artery aneurysm, persistent hemodynamic instability despite appropriate intensive care is an indication for surgery ( 3 ). Until now, almost all patients presenting ruptured ovarian artery aneurysm underwent exploratory surgery, and the most frequent treatment was adnexectomy and ligation of the artery, proximal and distal to the site of rupture ( 3 , 9 ). In our case, we could primarily perform angiography and embolization of the right ovarian artery, including the spontaneously ruptured ovarian aneurysm because the vital signs of the patient were stabilized after initial vigorous fluid resuscitation and transfusion and MDCT image exactly showed active bleeding, with a focus on the right ovarian artery aneurysm as the cause of the right retroperitoneal hematoma.…”
Section: Discussionmentioning
confidence: 99%
“…Coil with gelatin sponge particles were used in one ovarian artery in one patient ( 6 ). Kirk et al reported a case in which the left ovarian artery and ruptured aneurysm were embolized by particulates, Thrombin-JMI, because coil embolization was proved to be difficult, due to vessel tortuosity and spasm ( 9 ). In that case, incidentally, a right ovarian artery aneurysm was embolized electively by coils a week later ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation